Synthesis of Magnetic Nanosilica Material Based on River Sand to Improve Water Quality - Anggun Oktaviana; Lalu Ahmad Didik Meiliyadi; Bahtiar Bahtiar (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
Research has been carried out on the synthesis of river sand-based nanosilica magnetic material to improve water quality by utilizing iron sand taken from four rivers in the Lombok island region as a natural material for the water filtration process, this study aims to determine whether the iron sand nanosilica magnetic material able to improve the quality of well water or not. This study uses an experimental method where iron sand has gone through the coprecipitation process and the water quality parameters measured are temperature, pH and conductivity. The measurement results showed that well water after being mixed with iron sand decreased for temperature and conductivity parameters and increased for pH parameters. Of the three parameters, only one parameter does not meet the water quality standard requirements, namely the pH value before being mixed with iron sand which is below the standard, which is 6.32. However, after the well water was mixed with the four samples of river iron sand, the pH value increased to 7.99, 7.85, 7.75, and 8.00 so that it was able to meet water quality standards for pH parameters.